The Role of Good Corporate Governance in Enhancing the Performance of Village Credit Institutions - I Gede Cahyadi Putra; I Ketut Sunarwijaya; I Gusti Ngurah Bagus Gunadi (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2021)
Good corporate governance is corporate governance that explains the relationship between all interested parties in a regulated and organized business. The principles of good corporate governance should be also applied by village credit institutions to improve their performance. This research aims to examine and obtain empirical evidence of the influence of good corporate governance principles, including transparency, accountability, responsibility, independence, and fairness, on the performance of village credit institutions in Blahbatuh District. This study involved 36 samples of village credit institutions with 108 respondents, determined by saturated sample techniques. The data were analyzed by multiple linear regression after instruments and classical assumption testings. The results showed that the principles of good corporate governance have a positive effect on the performance of village credit institutions in Blahbatuh District.